Financial Deregulation and Household Saving. The Norwegian Experience Revisited - Elin Halvorsen (Statistics Norway, Research Department, 2003)
I use new micro data to study the effects of credit deregulation on the Norwegian household savings decline in the mid-1980s. This paper has three main findings. First, the decline in saving started in 1983, a couple of years earlier than previously thought on the basis of National Accounts data. Second, it was primarily young and middle-aged households who increased their consumption. Finally, the rapid increase in housing prices in 1985-86 may have been an important determinant of older and retired households' saving through reversed mortgages, but cannot on its own explain the decline in savings that started in 1983.
Keywords: D91; E21; E44; 330; Saving; consumption; financial deregulation; wealth effects and house prices.